Pengaruh Struktur Audit, Komitmen Organisasi, Dan Gaya Kepemimpinan Transformasional Pada Kinerja Auditor - Agung Dicky Wibawa, I Gusti Ngurah; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 24 No 3 (2018), 2018)
Population in this research is all auditor of public accountant office in Bali which incorporated in Indonesian Institute of Certified Public Accountant. Sampling method used is puposive sampling method, while data collected through questionnaire technique. Data analysis techniques used are quantitative analysis techniques that include multiple linear regression analysis. Target respondents of this research is 70 respondents, but the respondent data that can be processed is 53 respondents' answers. Testing the validity and reliability of the instruments of the variables used in this study has an acceptable level of validity and reliability. The results of this study indicate that the audit structure variable, organizational commitment, and transformational leadership style have positive and significant influence on auditor performance. This means that the use of the audit structure can help the auditor perform better in his duties, as well as the high level of commitment to his organization, the better performance, and the transformational leadership style can give a sense of the auditor's performance. Keywords : audit structure, organizational commitment, transformational leadership style, auditor performance.